NUTRITIONAL CHARACTERISTICS OF THE TWO FERMENTED FISH PRODUCTS - HENTAK AND NGARI OF MANIPUR. - SAROJNALINI, CH.; VISHWANATH, W. (Journal of Indian Fisheries Association, 2015)
Proximate composition and nutritional characteristics of the two fermented fish products Hentak and Ngari of Manipur (India) were evaluated. Percentage of moisture, protein, lipid and ash contents in Hentak and Ngari were respectively, 36.30 versus 36.03; 33.33 versus 38.38; 13.60 versus 13.34 and 11.43 versus 5.49. Digestibility values in feeding trials in laboratory rats for 28 days were 82.37% for Hentak 89.46% for Ngari and that of Casein was 92.69%. The biological value, food conversion ratio and protein efficiency ratio (PER) of Hentak were 96.94, 4.83 and 1.8 respectively and that of Ngari were 97.83, 3.17 and 1.8 respectively. The a amino nitrogen of Hentak and Ngari in Pepsin + Trypsin phase were 28.40 and 28.92 respectively. The TBA number, peroxide value and TVBN were within the acceptable limits.